Influence of exogenous growth-regulators on physiological and growth processes of dwarf mandarin cv. ‘Miagava-Vase’ - Belous, O.; Soytong, K.; Vasileyko, M. (International Journal of Agricultural Technology, 2021)
The influence of biologically active substances of a new generation as growth regulators on the process of ovary fall, improving the quality of fruits and increasing the adaptive potential of tangerine was investigated. The tested citrus plants are dwarf mandarin cv. ‘Miagava-Vase’. The tested plants have grown since in 1986 at Plantation of Subtropical Scientific Centre, Sochi, Russia. The experimental scheme clarified the three options as exogenous growth-regulators: obstaktin (5 ml/l water); nanoelicitor (1 ml/l water) and siliplant (5 ml/l water). The content of chlorophyll and carotenoids are determined; the assessment of the functional state of plants was carried out on the slow induction of chlorophyll fluorescence. It was found that the treatment of plants with growth regulators did not affect the content of green pigments in the leaves. In the processing microbial nanoelicitor and siliplant increased the number of carotenoids, thereby enhancing the defense reactions. Treatment with growth regulators led to an improvement in the functional state of plants, which was expressed in a higher value of the viability index, especially on variants with the introduction of nanoelicitor and siliplant. The treated citrus plants with siliplant resulted to the highest number of carotenoids increased in the leaves and followed by nanoelicitor. They imply as the activation of protective reactions to the plants. The slow chlorophyll fluorescence inductiuon expressed the higher viability index in siliplant than nanoelicitor and obstaktin. The photosynthetic activity index revealed that nanoelicitor and siliplant gave the highest activity and followed by obstaktin. The coefficient of photosynthetic activity expressed that nanoelicitor, siliplant and obstaktin were significantly higher than the control. Nanoelicitor showed significantly highest plant growth and followed by siliplant and obstaktin. Siliplant treatment confirmed significantly highest mass of fruits and followed by nanoelicitor and obstaktin. The fruits diameter was higher in siliplant than obstaktin and nanoelicitor. The treated citrus leaves with nanoelicitor encountered scoparone, a phytoalexin associated with resistance of Citrus to root rot.